2004
DOI: 10.1124/mol.65.4.999
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Rat Microglial Cells Synthesize the Endocannabinoid 2-Arachidonylglycerol, Which Increases Proliferation via a CB2Receptor-Dependent Mechanism

Abstract: Microglia, as phagocytes and antigen-presenting cells in the central nervous system, are activated in such disease processes as stroke and multiple sclerosis. Because peripheral macrophages are capable of producing endocannabinoids, we have examined endocannabinoid production in a macrophage-colony stimulating factor (M-CSF)-dependent rat microglial cell line (RTMGL1) using reversed phase high-pressure liquid chromatography and liquid chromatography-mass spectroscopy. We determined that cultured microglial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
203
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(213 citation statements)
references
References 44 publications
5
203
1
4
Order By: Relevance
“…Several mitogens are also known to positively regulate the proliferation of NSPCs in the SVZ, e.g., erythropoietin (Wang et al, 2004), vascular endothelial growth factor (VEGF) (Jin et al, 2002) and endocannabinoids (Carrier et al, 2004, Aguado et al, 2005. We found that microgliaconditioned medium had additive effects on cell proliferation in the neurospheres in the presence of high concentrations of EGF/bFGF, suggesting that the unknown factor acts via a different pathway.…”
Section: Microglia Activated By Brain Injury Secrete Factors Promotinmentioning
confidence: 72%
“…Several mitogens are also known to positively regulate the proliferation of NSPCs in the SVZ, e.g., erythropoietin (Wang et al, 2004), vascular endothelial growth factor (VEGF) (Jin et al, 2002) and endocannabinoids (Carrier et al, 2004, Aguado et al, 2005. We found that microgliaconditioned medium had additive effects on cell proliferation in the neurospheres in the presence of high concentrations of EGF/bFGF, suggesting that the unknown factor acts via a different pathway.…”
Section: Microglia Activated By Brain Injury Secrete Factors Promotinmentioning
confidence: 72%
“…These data suggest that cannabinoids regulate glial activity primarily through CB2 receptors. Glial cells not only receive cannabinoid signals but can themselves produce cannabinoids such as anandamide [189], 2-AG [190] and palmitoylethanolamide [191], and also express the enzymes involved in the synthesis and degradation of endocannabinoids [192][193][194]. Because both neurons and glia express elements of the cannabinoid system, it was hypothesized that the cannabinoid system plays an important role in neuron-glia communication.…”
Section: (D) Regulation Of Glial Activitymentioning
confidence: 99%
“…The effects of endocannabinoids on microglia proliferation were studied by Carrier et al [8], who found that 2-AG, but not anandamide, stimulated a concentration-dependent increase in proliferation in microglial cells cultured in the presence of mononuclear colony stimulating factor (M-CSF). This is in contrast to McKallip et al [39], who showed that cannabinoids inhibit the proliferation of cultured macrophages.…”
Section: In Vitro Studiesmentioning
confidence: 99%